2011
DOI: 10.1177/1750635211420629
|View full text |Cite
|
Sign up to set email alerts
|

Proactive crisis communication? News coverage of international conflicts in German print and broadcasting media

Abstract: This study examines the ambitions of proactive crisis communication in the realm of international conflicts. Based on the concept of peace journalism, the authors analyse whether German media coverage on international conflicts complies with normative demands. So far, most studies have investigated the media’s role during the climactic stages of conflicts and have neglected the pre- and post-escalation phases. Therefore, the study distinguishes four specific phases of a conflict. With regard to news value theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Segev, 2015). The only study explicitly linking eventand context-oriented characteristics to news coverage on conflicts was conducted by Zillich et al (2012), who content analyzed seven German media outlets (four television broadcasters, three national newspapers) and determined the share of various news factors within media coverage (status of nations involved, reach, damage, aggression, benefit). They found that reach (the extent to which the population was affected) was by far the most prevalent factor in foreign news about wars, whereas the importance of the other factors depended on the conflict phase.…”
Section: The International Flow Of Newsmentioning
confidence: 99%
“…Segev, 2015). The only study explicitly linking eventand context-oriented characteristics to news coverage on conflicts was conducted by Zillich et al (2012), who content analyzed seven German media outlets (four television broadcasters, three national newspapers) and determined the share of various news factors within media coverage (status of nations involved, reach, damage, aggression, benefit). They found that reach (the extent to which the population was affected) was by far the most prevalent factor in foreign news about wars, whereas the importance of the other factors depended on the conflict phase.…”
Section: The International Flow Of Newsmentioning
confidence: 99%
“…However, according to Galtung (2002), a peace journalism approach includes media coverage that aims for the solution and de-escalation of conflicts which depends on media coverage prior to the conflict as well as after the conflict occurs. Taking a qualitative approach, Zillich et al (2011: 263) analyzed German media coverage of international conflicts and discovered that international conflicts are very rarely covered once they have been settled even though journalists acknowledge the possibility of contributing to peaceful resolutions, particularly when their news coverage occurs during the phase of reconciliation. Furthermore, Shaw and Martin (1993) reported that studies investigating the media’s coverage of conflict at stages other than during the escalating phase are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Carter, Thomas, and Ross (2011) with Marsden and Savigny (2009) found that the media has the ability to set the stage for future conflict by quietly portraying oppositional relations between two conflicting groups. Zillich's study in Germany and Fernandez-Villanueva's study in Spain showed that in reporting conflicts, media tend to exaggerate the conflict event which in turn escalates the conflict instead of solving it (Zillich, Gobbel, Stengel, Maier, & Ruhrmann, 2011). A study from Milioni, Doudaki, Tsiligiannis and Vadratsikas (2015) in Cyprus even found that the media can play a role in reconstructing conflict.…”
Section: Literature Review Media and Conflictmentioning
confidence: 99%